APLIKASI PENGOLAHAN DATA REKAM MEDIS PASIEN PADA PUSKESMAS TEGAL ARUM KECAMATAN RIMBO BUJANG KABUPATEN TEBO - Nurjani, Yeni; Sihombing, Johannes Josua (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2019)
Medical record information system in Tegal Arum Rimbo Subdistrict health centers of the young Kabupaten Tebo is a system designed to makes the recording, processing, and report rendering penyamapaian patient medical information needed for the activities of the clinic.This system is developed by using Microsoft Visual Basic 6.0 program and Program My SQL create database. This system is very important to make it easy to manage medical record data quickly and efficiently.Data areas in Tegal Arum Rimbo Subdistrict health centers of the young Kabupaten Tebo are still manually so there is still an error in the data storage and management of medical record (human error).The design of this medical record information system aims to make it easier to enter and manipulate data in the medical record and displays the reports required by the clinic.Development of the medical record information system was designed using the method of System development life cycle (SDLC) which consists of three main stages of analysis, design, and implementation.The results of the medical record information system pemrrograman this is an application to perform the recording of the patient's medical record out and can display a report that consists of patient data reports based on date of admission, outpatient data reports.The design of the system is expected to simplify the process of managing the medical record data and create reports in public health to produce accurate data.